CUNEIFORM AND OLD TESTAMENT: THREE NOTES - Burrows, Eric (The journal of theological studies, 1927)
ERIC BURROWS, S.J.; CUNEIFORM AND OLD TESTAMENT: THREE NOTES, The Journal of Theological Studies, Volume os-XXVIII, Issue January, 1 January 1927, Pages 184–185